PERAN NAHDLATUL ULAMA DALAM PENGUATAN NILA-NILAI MODERASI BERAGAMA - Yatasha, Yazkiyyah; Zuhri, Ahmad; Faza, Abrar M. Dawud (Studia Sosia Religia, 2023)
Nahdlatul Ulama is the largest Islamic organization in Indonesia. The existence of Nahdlatul Ulama always unites itself with the struggle of the nation, placing NU and all its citizens to be active in the nation-building division towards a just and prosperous society that is blessed by Allah SWT. In North Sumatra, NU is one of the largest and most influential organizations for Muslims. NU with its Ahlussunnah Wal Jama'ah understanding, which is known as moderate, stands at the forefront and becomes a bulwark for the integrity of the nation by developing the notion of moderation. However, the fact is that the application of religious moderation is still a discourse for Islamic organizational institutions, especially Islamic institutions in the city of Medan, because until now there has been no real evidence of Islamic institutions implementing religious moderation.The questions in this research are; 1) What is the Existence of Nahdatul Ulama in Medan City?; 2) What is the potential of the Nahdlatul Ulama Institution in Strengthening the Values of Religious Moderation in Medan City?.This research method is qualitative, which the author uses is a religious phenomenological approach while the theory approach is interaction.The conclusion in this study is that the strengthening of religious moderation values of Nahdlatul Ulama in Medan City always displays two characters (wisdom and flexibility). For Medan City Nahdlatul Ulama, wisdom is an action that is conducive to obtaining benefits/avoiding harm, while flexibility is a compromising attitude and avoiding all forms of extremism. One of NU's national political ijtihad is the obligation to reduce or even avoid all forms of risk or bad consequences (fiqh rules: dar'ul mafasid muqaddamun ala jalbil mashalih). In addition, the potential of NU institutions in strengthening the values of religious moderation in Medan City which includes providing social assistance to all circles of society, helping each other among others is an activity in instilling the values of religious moderation. Implementation of the Values of Religious Moderation is recognizing the rights of others, respecting other people's beliefs, agreeing on differences, understanding each other.